Oxytocin 10 IU as Prophylactic for Uterine Atony : a Randomized Clinical Trial: Oksitosin 10 IU sebagai Profilaksis Atonia Uteri : suatu Uji Coba Klinis Acak - Ridwan A. Putra; Iskandar Zulqarnain; Zaimursyaf Azis; Jusuf S. Effendi; Wiryawan Permadi; Ria Bandiara (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective : To compare the effectiveness of oxytocin dose of 10 IU and 20 IU for preventing uterine atony in women undergoing cesarean section. Methods : This was a double-blind, randomized clinical trial with good matching selection with randomization block of patients who had risk factors for the occurrence of uterine atony such as preeclampsia, patients were receiving MgSO4, oxytocin intrapartum and chorioamnionitis who performed stratified randomization prospectively with two kinds of oxytocin doses which are 10 IU and 20 IU as a prophylaxis for uterine atony in women who performed emergency cesarean section with transverse incision and were using a general anesthesia. Results : This study found no any significant differences between the use of 10 IU and 20 IU as prophylaxis for uterine atony during cesarean section either in its action at the time or while in recovery room, especially on the cases without chorioamnionitis thus using oxytocin 10 IU regimen can be considered, besides the effectiveness did no differ, it will cost cheaper than oxytocin 20 IU regimen which frequently used. Conclusions : There were no significant differences in the incidence of blood loss during the cesarean section between the treatment of oxytocin 10 IU group and oxytocin 20 IU group. The additional uterotonic was using during the action of the cesarean section between the treatment of oxytocin 10 IU group, and oxytocin 20 IU group gave no significant differences. The side effects in this study at least form of chills and vomiting found no significant differences between both of groups despite the side effects that arise in oxytocin 20 IU group was higher at 23.08% than oxytocin 10 IU group at 15.19%. Chorioamnionitis would be a risk factor for the occurrence of uterine atony during the action of the cesarean section if it associated with the use of additional uterotonic in oxytocin 10 IU group if compared with oxytocin 20 IU group. Keywords : cesarean section, oxytocin, uterine atony. Abstrak Tujuan : Untuk membandingkan efektifitas penggunaan dosis 10 IU dan 20 IU sebagai profilaksis atonia uteri pada saat seksio sesarea. Metode : Penelitian ini menggunakan uji klinis acak ganda dengan seleksi yang sesuai dengan blok acak pada pasien-pasien yang memiliki faktor risiko terjadinya atonia uteri seperti preeklamsia, pasien yang diberikana MgSO4 dan oxytocin intrapartum sebelumnya serta chorioamnionitis yang dilakukan pengacakan secara prosfektif bertingkat yang diberikan dua jenis dosis oksitosin yaitu 10 IU dan 20 IU sebagai profilaksis atonia uteri pada perempuan yang dilakukan seksio sesarea darurat dengan insisi transversal dan menggunakan anestesi umum. Hasil : Penelitian ini menemukan tidak adanya perbedaan yang bermakna antara penggunaan dosis oksitosin 10 IU dan 20 IU sebagai profilaksis atonia uteri pada seksio sesarea baik saat tindakan operasi maupun saat berada di ruang pemulihan, terutama pada kasus-kasus tanpa khorioamnionitis dimana memerlukan oksitosin tambahan pada kelompok 10 IU, selain efektifitasnya tidak berbeda, akan lebih murah dari pada rejimen oksitosin 20 IU yang sering digunakan saat ini. Kesimpulan : Berdasarkan hasil penelitian ini, tidak ada perbedaan yang bermakna dalam kejadian kehilangan darah selama operasi seksio sesarea antara perlakuan kelompok oksitosin 10 IU dan kelompok oksitosin 20 IU. Penggunaan uterotonik tambahan selama tindakan seksio sesarea antara perlakuan kelompok oksitosin 10 IU dan kelompok oksitosin 20 IU tidak memberikan perbedaan yang signifikan. Efek samping dalam penelitian ini yakni menggigil dan muntah, tidak ditemukan perbedaan yang bermakna antara kedua kelompok meskipun efek samping yang muncul pada kelompok oksitosin 20 IU lebih tinggi 23,08% dibandingkan kelompok oksitosin 10 IU pada 15,19%. Khorioamnionitis merupakan faktor risiko terjadinya atonia uteri selama tindakan seksio sesarea jika dikaitkan dengan penggunaan uterotonika tambahan pada kelompok oksitosin 10 IU jika dibandingkan dengan kelompok oksitosin 20 IU. Kata kunci : atonia uteri, oksitosin, seksio sesarea.